Distribución geográfica etaria y racial de la hemoglobina S en Brasil. - Alvares Filho, F.; Naoum, P. C.; Moreira, H. W.; Cruz, R.; Manzato, A. J.; Domingos, C. R. (My University, 1995)
OBJECTIVES: This paper was meant to analyse distribution of HbS carriers in Brazil, comprising its regional prevalence and the relationship with racial settlement and age groups. MATERIAL AND METHODS: 67,667 blood samples from 48 Brazilian towns were analysed from 1976 to 1988. Such samples were classified as Caucasoid and Negroid. The diagnosis was defined by means of qualitative electrophoresis in alkaline and acid pH, quantification of haemoglobin fractions, cytological studies and some cases were confirmed after examination of the parents. RESULTS: The study of those 67,667 samples allowed us to detect 1,492 HbS carriers (2.2%). That frequency is higher among Negroids (5.16%) than among Caucasoids (1.22%): Z = 22.1397 (Zcritical; 0.05 = 1.9600). Taking the HbS carrier distribution into consideration, we noticed that it is relatively homogeneous among Negroids and higher than 5% in 9 out of the 16 areas involved in the study. By classifying the age group of the areas in the general sample and by comparing the proportions, we found out that there are significant differences (chi 2 = 50.88; chi 2 critical; 0.05; 5 gl = 11.070). CONCLUSIONS: Sickle-cell anaemia diseases play an important role among the pathologies found in several countries, including Brazil. This paper shows that the carriers prevalence varies in the several areas under study and is higher among Negroids in almost all of them. The decreasing frequency occurring from North to South in the general samples and among Caucasoids may be assigned to the contribution of the Negroes in the interracial crossing, particularly in the Northeast.
Age and racial geographic distribution of S hemoglobin in Brazil
Keywords: hemoglobin S; age distribution; Brazil; Caucasian; human; negro; prevalence; Age Distribution; Caucasoid Race; English Abstract; Hemoglobin, Sickle; Human; Negroid Race; Prevalence